Characterization and Stability Analysis of Rock Mass Discontinuities in Layered Slopes: A Case Study from Fushun West Open-Pit Mine - Ming Li; Zhanguo Xiu; Jianhua Han; Fanzhen Meng; Feili Wang; Hongguang Ji (Applied Sciences)
Discontinuities exist widely in high rock slopes and threaten their stability at all times. To accurately characterize the information of rock mass discontinuities in high slopes, the layered rock slope on the north side of the Fushun West Open-pit Mine was taken as a typical sample, the high-definition images were collected using unmanned aerial vehicle (UAV) photogrammetry technology, and the Agisoft PhotoScan software was then used to generate the 3D rock slope model (i.e., 3D point cloud data) in this study. After the noise reduction processing of the generated rock slope model, the orientation and dominant grouping of the rock mass discontinuities were calculated by the KNN (K-nearest neighbor) search and the PCA (principal component analysis) algorithms, and the calculated results are calibrated with manual measurements in the local slope area. Moreover, the high-definition images containing different rock layers were selected to identify the detailed information of the rock discontinuities using the MATLAB program. This study shows that the orientation information of the rock discontinuities extracted from point cloud data are close to the corresponding result of manual measurements. There are great differences in the orientation of the discontinuities at different rock layers. The small-angle discontinuities are densely distributed in brown shale, which has a serious influence on the stability of the cracked rock slope. This research can provide a reference for the stability analysis of layered rock slopes and the prevention of landslide disasters in the Fushun West Open-Pit Mine.